PENGEMBANGAN PERANGKAT PEMBELAJARAN IPA TERPADU BERBASIS INKUIRI TERBIMBING DAN SALINGTEMAS UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS DAN HASIL BELAJAR KOGNITIF PESERTA DIDIK SMP - Laila Khusnah (JURNAL BIOSHELL, 2015)
The research aims to produce the integrated instructional kitfor natural science based on guided inquiryand sets learning approachesin order to be able to increase science psychomotor process andstudents’cognitive learning result. This research uses 4D model development research design from Thiagarajan, that is limited only to the ‘develop’ level. The instructional kitdeveloped are validated by the expert in the instructional kit, the expert in the subject, the science teacher, and then practically tested to the students of class VIII of SMPN 2 Jember at 2013/2014. The validation test results from all validators show that theintegrated instructional kitfor natural science based on guided inquiry and sets learning approacheshas categorized sufficiently valid. The practical test results show that the integrated instructional kit for natural science based on guided inquiryand sets is effectively used on learning process because it is able to increase the science psychomotor process and students’cognitive learning result.Keywords: developing instructional kit, guided inquiry and sets learning approaches, science psychomotor process, students’ cognitive learning result.